Determinants of vegetarianism and partial vegetarianism in Ireland - Eimear Leahy; Seán Lyons; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2011)
Vegetarianism is increasing in the western world. Anecdotally, this trend can be attributed to heightened health, environmental and animal welfare concerns. In this paper we investigate the factors associated with vegetarianism among adults in Ireland. Using the 2007 Survey of Lifestyles, Attitudes and Nutrition, we use a logit model to assess the relationship between vegetarianism and the socioeconomic and personal characteristics of the respondents. We also analyse the factors associated with varying levels of meat consumption using an ordered logit model. This paper adds to the existing literature as it is the first paper to estimate the determinants of vegetarianism and partial vegetarianism in Ireland.
Keywords: 330